2021
DOI: 10.1039/d0cy01969k
|View full text |Cite
|
Sign up to set email alerts
|

Formic acid enabled selectivity boosting in transfer hydrogenation of 5-hydroxymethylfurfural to 2,5-furandimethanol on highly dispersed Co–Nx sites

Abstract: Catalytic transfer hydrogenation (CTH) reaction is considered as a potential route for upgrading bio-based carbonyl compounds to their corresponding alcohols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 58 publications
4
30
0
Order By: Relevance
“…A series of copper-cobalt bimetallic catalysts was prepared with different Cu/Co ratios, and their XRD patterns are shown in Figure 2 . The diffraction peaks at 43.3°, 50.4°, and 74.1° are attributed to metallic copper (PDF #89-4307) ( Chen et al, 2020 ; Rao et al, 2020 ; Xu et al, 2021 ), and those at 44.2°, 51.5°, and 75.9° are attributed to metallic cobalt (PDF #89-2838) ( Chen et al, 2017 ; Solanki and Rode, 2019 ). It can be observed that mono metal catalyst Cu–IG contains only metallic copper diffraction peak, while Co–IG catalyst contains only metallic cobalt diffraction peak.…”
Section: Resultsmentioning
confidence: 99%
“…A series of copper-cobalt bimetallic catalysts was prepared with different Cu/Co ratios, and their XRD patterns are shown in Figure 2 . The diffraction peaks at 43.3°, 50.4°, and 74.1° are attributed to metallic copper (PDF #89-4307) ( Chen et al, 2020 ; Rao et al, 2020 ; Xu et al, 2021 ), and those at 44.2°, 51.5°, and 75.9° are attributed to metallic cobalt (PDF #89-2838) ( Chen et al, 2017 ; Solanki and Rode, 2019 ). It can be observed that mono metal catalyst Cu–IG contains only metallic copper diffraction peak, while Co–IG catalyst contains only metallic cobalt diffraction peak.…”
Section: Resultsmentioning
confidence: 99%
“…[20] Utilizing FA as the hydrogen donor, Xu et al also used Co in the synthesis of catalysts and produced ordered mesoporous Ndoped carbon-constrained CoÀ N x (CoÀ NC) as catalysts. [23] Using the Co(phen) 2 (OAc) 2 complex as the Co precursor and SBA-15 as the hard template, 86 % yield of 2,5-furandimethanol (FDM) was obtained at 160 °C, 5 h in 1,4-dioxane via an intermolecular hydride transfer mechanism, similar to the Meerwein-Ponndorf-Verley (MPV) mechanism. Compared to the molecular hydrogen, FA facilitated HMF hydrogenation but restrained FDM hydrogenolysis, which can lead to a higher yield of FDM.…”
Section: Formic Acid As Hydrogen Donormentioning
confidence: 99%
“…Compared to the molecular hydrogen, FA facilitated HMF hydrogenation but restrained FDM hydrogenolysis, which can lead to a higher yield of FDM. [23] From the hydrogenation process of HMF to DMF in formic acid, 5-formyloxymethylfurfural (FMF) is a fairly critical intermediate. HMF and FMF are equivalent precursors to DMF.…”
Section: Formic Acid As Hydrogen Donormentioning
confidence: 99%
“…Owing to the abundance of exposed co-active sites, the catalyst showed remarkable performance as well as stability. Similarly, Xu et al also developed highly dispersed Co-Nx sites on mesoporous carbon for catalytic transfer hydrogenation (Xu et al 2021). The catalyst demonstrated excellent performance as it could convert up to 100% 5-hydroxymethylfurfural with an 86% yield of 2,5-furandimethanol.…”
Section: Mesoporous Carbonmentioning
confidence: 99%